(untitled) (GEOgraphia, 2021)
Este artigo contempla as grandes divergências que envolvem a abordagem material da cultura e sua desconstrução, por intermédio da avaliação da influência da virada cultural e da Nova Geografia Cultural. Sua relevância reside no fato destas divergências impactarem severamente nas modernas abordagens culturais da Geografia. Conclui-se que, para além da discussão da materialidade da cultura, a apregoada incompatibilidade entre o cultural e o social nas abordagens da Geografia Cultural é falsa, à medida que a reflexão não ontológica pode centrar-se nos efeitos sociais da materialidade mítica. Palavras-Chave: Virada Cultural; Nova Geografia Cultural; Materialidade; Ontologia. BETWEEN THE CULTURAL AND THE SOCIAL IN GEOGRAPHICAL APPROACHES Abstract: This article contemplates the great divergences that involve the material approach of culture and its deconstruction, through the evaluation of the influence of the cultural turn and the New Cultural Geography. Its relevance lies in the fact that these divergences have a severe impact on modern cultural approaches to Geography. It is concluded that, in addition to discussing the materiality of culture, the incompatibility between the cultural and the social in the approaches of Cultural Geography is false, as the non-ontological reflection can focus on the social effects of mythic materiality. Keywords: Cultural Turn; New Cultural Geography; Materiality; Ontology. ENTRE LO CULTURAL Y LO SOCIAL EN ENFOQUES GEOGRÁFICOS Resumen: Este artículo contempla las grandes divergencias que envuelven el enfoque material de la cultura y su deconstrucción, a través de la evaluación de la influencia del giro cultural y de la Nueva Geografía Cultural. Su relevancia radica en el hecho de que estas divergencias tienen un impacto severo en los enfoques culturales modernos de la Geografía. Se concluye que, además de la discusión sobre la materialidad de la cultura, la pretendida incompatibilidad entre lo cultural y lo social en los enfoques de la Geografía Cultural es falsa, pues la reflexión no ontológica puede enfocarse en los efectos sociales de la materialidad mítica. Palabras clave: Giro Cultural; Nueva Geografía Cultural; Materialidad; Ontología.